INVESTORS’ BEHAVIOR IN THE CONTEXT OF STOCK MARKET— A REACTION TO THE CHANGE OF CEO ANNOUNCEMENTS - Yang, Ni (2017)
ABSTRACT CEO is the most eye-catching person to the investors, scholars, and practitioners. The impact of changing a new CEO on the movement in the value of the relevant share price is studied in this dissertation. An event study has been applied to capture the effect of CEO change event through a cross-country and industry level with unique hand-collected data. This work extends existing work that focuses on CEO succession issue.